Archenemies - Meyer, Marissa (Meyer, Marissa. Renegades (Series), 2018)
As Nova, Adrian, and the rest of their crew face escalating crime in Gatlon City, covert weapons and conflicting missions have Nova and Adrian questioning not only their beliefs about justice, but also their feelings for each other.